COVID 19 and rural India: better now than later - Naik, Gitismita; Kumar, M. Mohan (International Journal Of Community Medicine And Public Health, 2020)
COVID 19 is devastating lives worldwide and India is no exception. Government of India on 15th April classified districts as hotspots or red zones (123 districts with large outbreaks and 47 with clusters) and non-hotspots or orange zones (207 districts). This leaves more than 300 of the country’s 731 districts which are not yet affected by the pandemic, classified as non-infected districts or green zones. Of India’s 1.21 billion people, about 376 million people live in the districts now classified as green zones and while 68.8% of India’s population lives in rural areas (Census 2011), the share of rural population in the green zones is relatively higher at 84%. This stands true across big states, Kerala being the only exception. It is this proportion of population who has to be protected in the battle against COVID 19 to ultimately emerge victorious and limit any further spread.